PHYSICAL EDUCATION IN SCHOOL DYNAMICS: BUILDING KNOWLEDGE IN HUMAN MULTIDIMENSIONALITY (Fiep Bulletin - online, 2012)
This paper aims to present the relevance of school physical education for 54 students from 3rd grade of primary school, a public school in Natal-RN, considering the construction of knowledge in the different human dimensions. It is part of a study that has identified how to build solidarity from the school Physical Education. Methodological option was to collaborative research that had the press conference, in groups of five students, such as instrumentation. Thirty-five percent of these students indicated Physical Education as the first choice of course they like, which confirms the wide acceptance of this as a motivator element for these students, explained in their justification, "because it's cool, you learn good things and have fun.” What they like in Physical Education indicates a universe of reasons that show how the content of programming, the dynamics of teaching and the relationship with teachers have influenced this choice. Of one hundred and fifty indications of contents learned, 66% fall in the general education knowledge, from being and living and from solidarity, while 34% refer to the specific contents of Physical Education. Among the general knowledge of education, they were grouped into four major areas: being polite to 9% of indications, the education from being and live with to 47%; education for sympathizing with 10%; and finally, education from human motility with 34%. What you learned with physical education in the voices from students that participated of the scope of this study demonstrate that the teaching-learning process held by teachers has reached students in different spheres of knowledge.
Keywords: Physical Education; School; Knowledge in Human Multidimensionality